Outcomes of Top-Down Holmium Laser Enucleation of Prostate for Recurrent/Residual Benign Prostatic Hyperplasia: One-Year Follow-Up. (20th September 2022) - Zakaria, Ahmed S.; Hodhod, Amr; Abbas, Loay; Fathy, Moustafa; Abdul Hadi, Ruba; Shabana, Waleed; MacDonald, Anastasia Alexandra; Gamaleldin, Ahmed; Abdallah, Mohamed; Elgharbawy, Mohamed; Ahmad, Abdulrahman; Roos, Adam; et al.
Abstract : Introduction and Objective . We aimed to evaluate urinary functional outcomes of top-down holmium laser enucleation of the prostate (HoLEP) in patients who underwent transurethral resection of the prostate (TURP) for the management of benign prostatic hyperplasia (BPH) compared to patients with primary BPH. Materials and Methods . We carried out a retrospective analysis of patients who underwent top-down HoLEP for the management of recurrent BPH at our institution. Patients who had previously undergone TURP were assigned to group I, while those with no history of prostate surgery were allocated to group II. Preoperative clinical characteristics, enucleation time, resected tissue weight, morcellation time, energy used, and intraoperative and postoperative complications were recorded and statistically analyzed. Patients were followed up postoperatively at 1, 3, 6, and 12 months. The evaluation included the International Prostate Symptom Score (IPSS), quality of life assessment (QoL), maximum urinary flow rate ( Q max ), postvoid residual urine test (PVR), and continence status. Results . Two hundred and sixty-nine patients were included in this study. Group I consisted of 68 patients with recurrent BPH, while group II included 201 patients. There were no statistically significant differences in preoperative characteristics between both groups. The median enucleation time for group I (67.5 min (25–200)) was not significantly longer than that for group II (60 min (19–165) (p = 0.25 )). Operative outcomes, including morcellation time, resected weight, catheter duration, and hospital stay, were comparable between both groups. At 1, 3, 6, and 12 months, all urinary functional outcomes showed significant improvement, and there were no significant differences between the two groups. At 3 months' follow-up, two patients in group I and three patients in group II experienced stress urinary incontinence (SUI). At the last follow-up visit, one patient from group I presented with persistent SUI. Conclusions . For managing recurrent and nonrecurrent cases of BPH, top-down HoLEP is safe with comparable urinary functional outcomes. Patients with a history of previous prostate surgery can be counselled that their prior transurethral procedure does not reduce the benefits of HoLEP.